A Deep Learning Quantification Algorithm for HER2 Scoring of Gastric Cancer - Han, Zixin; Lan, Junlin; Wang, Tao; Hu, Ziwei; Huang, Yuxiu; Deng, Yanglin; Zhang, Hejun; Wang, Jianchao; Chen, Musheng; Jiang, Haiyan; Lee, Ren-Guey; Gao, Qinquan; et al. (Frontiers in Neuroscience, 2022)
Gastric cancer is the third most common cause of cancer-related death in the world. Human epidermal growth factor receptor 2 (HER2) positive is an important subtype of gastric cancer, which can provide significant diagnostic information for gastric cancer pathologists. However, pathologists usually use a semi-quantitative assessment method to assign HER2 score of gastric cancer by repeatedly comparing hematoxylin and eosin (H&E) whole slide images (WSIs) with their HER2 immunohistochemical WSIs one by one under the microscope. It is a repetitive, tedious and highly subjective process. Additionally, WSIs have billions of pixels in an image, which poses computational challenges on Computer-Aided Diagnosis (CAD) systems. This study proposed a deep learning algorithm for HER2 quantification evaluation of gastric cancer. Different from other studies that use convolutional neural networks for extracting feature maps or pre-processing on WSIs, we proposed a novel automatic HER2 scoring framework in this study. In order to accelerate the computational process, we proposed to use the re-parameterization scheme to separate the training model from the deployment model, which significantly speedup the inference process. To the best of our knowledge, this is the first work to provide a deep learning quantification algorithm for HER2 scoring of gastric cancer to assist the pathologist's diagnosis. Experiment results have demonstrated the effectiveness of our proposed method with an accuracy of 0.94 for the HER2 scoring prediction.